(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The article addresses the implementation of modern management practices and technologies in various industries. The paper examines how new approaches such as digitalization, agile management, and data-driven decision-making enhance organizational performance, adaptability, and competitiveness. The article presents real-world examples and integration issues, proposing recommendations for successful adoption and sustainable development.